AB0592 Evaluation of Arterial Stiffness in A Cohort of Systemic Sclerosis Patients: A Case-Control Study. (15th July 2016) - Bartoloni, E.; Battista, F.; Alunno, A.; Cannarile, F.; Valentini, V.; Pucci, G.; Schillaci, G.; Gerli, R.
Abstract : Background: Systemic sclerosis (SSc) patients are characterized by premature cardiovascular (CV) mortality. In this setting, the disease represents an intriguing model to evaluate premature endothelial damage. Indeed, both macrovascular and microvascular damage characterizes subclinical atherosclerosis (ATS) in these patients (1). Traditional CV risk factors, SSc-related inflammatory and autoimmune mechanisms may contribute to accelerated ATS. Among indirect measures of subclinical ATS, aortic stiffness (AS), measured by carotid-femoral pulse wave velocity (cf-PWV), and augmentation index (Aix@75) are independent predictors of CV morbidity and mortality in several diseases. To date, studies evaluating subclinical ATS in SSc provided conflicting results. Moreover, factors influencing atherosclerosis in SSc have not been well defined. Objectives: To evaluate cf-PWV and Aix@75 measures of AS in SSc patients and analyze relationship between disease-related features and AS. Methods: Thirty-four consecutive female SSc patients (mean age 61±15 years) with mean disease duration of 17±12 years since Raynaud phenomenon and 34 healthy sex, age and arterial pressure (AP) matched controls (HC) were enrolled. Traditional CV risk factors, disease-specific clinical, metabolic and immunologic features were collected. Disease activity and severity were assessed by Valentini Disease Activity Index (VDAI) and Medsger Disease Severity Scale (MDSS), respectively. Cf-PWV was determined by means of applanation tonometry (SphygmoCor). AIx@75 was calculated as difference between the 2nd and 1st wave systolic peaks and standardised to 75 beats/min. The relationship between cf-PWV, AIx@75 and all variables was investigated with univariate (one-way ANOVA) and multivariate models. Results: Mean blood AP was similar in patients and HC. About 1/3 patients were receiving immunosuppressive therapy, 33% iloprost, 41% calcium-chanel blockers, 9% beta-blockers, 9% angiotensin receptor blockers and 3% ACE-inhibitors. Mean VDAI was 1, 37±1, 32 and 15% of patients were characterized by high activity (score >3). Mean MDSS was 0, 35±0, 65 with 9% of patients who had a moderate-severe disease. Both absolute AIx (16, 1±8 vs 11, 5±7 mmHg; p=0, 014) and AIx@75 (30, 9±16 vs 22, 2±12%; p=0, 012) resulted significantly higher in SSc compared to HC, while cf-PWV was similar in the two populations. At multivariate analysis, age, mean AP and mean C-reactive protein resulted independent predictors of cf-PWV, while only age and mean AP of AIx@75. Of interest, limited SSc and anti-centromere positive patients were characterized by significantly higher AIx@75 in comparison to diffuse SSc and anti-Scl70 positive (p=0.045 and p=0.04, respectively). Conclusions: Subclinical atherosclerotic damage in SSc seems to be mainly characterized by increased AIx, a measure of arterial stiffness that encompasses peripheral vascular reflectance and left ventricular ejection, thus reflecting a prevalent peripheral microvascular involvement. Moreover, several factors, including inflammatory state, may contribute to AS in these patients. Intriguing, the significant increase of AIx in limited SSc may suggest a more severe peripheral microvascular involvement in these patients. References: Cannarile F et al. Ann Transl Med 2015;3:8. Disclosure of Interest: None declared